A study on the challenges of implementing green building concept in Sarawak, Malaysia - Lee, Yee Yong; Ikqmal Azmi, Muhd Syaznie Ikqmal Azmi1; Lee, Yeong Huei (2020)
Malaysia is looking forward in achieving developed country status which drives several strategic plans in construction, as it plays a vital role in country‟s economic growth and development. Construction Industry Transformation Programme (CITP) has been introduced to boost its performance with sustainable construction. However, most of the construction industry players are not involved in sustainable construction especially on green building concept and thus decelerating the development. Therefore, this study is conducted to identify the drivers and challenges faced by the construction industry players through questionnaire survey where the market demand from stakeholders is placed primarily in implementing green building. The findings showed that awareness and understanding of the stakeholders about green building concept are lacked due to unforeseen circumstances. Detail explanations or descriptions on the benefits and contributions from green building application are needed to be delivered to stakeholders. A framework is proposed for future implementation by improving the education and delivered information, as well as providing the mechanism of promoting the green building concept among the stakeholders.